Writing Application in English Language Teaching: A Systematic Literature Review From 2013-2024 - Lita Saleppang; Salasiah Ammade (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2025)
This article aims to examine the development and application of digital applications in teaching English writing skills, focusing on two main categories: web-based applications and mobile applications. This study uses a literature review approach analyzed through literature mapping from the Connected Papers platform, with publications ranging from 2013 to 2024. The findings indicate that web-based applications such as Google Docs and Canvas significantly enhance students' writing skills through online collaboration, real-time feedback, and structured revision processes. On the other hand, mobile applications such as WhatsApp and Google Slides support writing skills in a more flexible informal context, emphasizing social interaction, collaboration, and out-of-class learning engagement. Both types of applications have their own advantages and challenges and can be used complementarily in hybrid and adaptive English writing instruction. The implications of these findings highlight the importance of technology-responsive instructional design, teacher training in digital literacy, and pedagogical adaptation to students' social and cultural contexts. This article recommends further research on the long-term effectiveness of digital applications in improving students' writing competencies, as well as the development of sustainable and inclusive implementation strategies in ESL and EFL learning environments.